(untitled) (Journal of Social Sciences Review, 2023)
With the advancements in science and technology, novel opportunities for improving human life style are on rise. These opportunities proures betterment in social and cultural spheres of life but at the same time, these serve as a gateway to many social, cultural and religious issues by posing serious threat to divine eastablished norms and religious values. Static Picturization is one the emerging businesses; many people are earning a living from it. The Holy Qur’an does not mention its sanctity, and in the hadith of the Prophet, the sayings of the Prophet have been mentioned at various places about the sanctity of photography. The issue under discussion will be a discussion about the Shariah status of photography. As time goes by, the problems regarding it are increasing day by day and new debates are getting origins. Islam is progressive religion that realize the vitality of industrial revolution and stresses to device methods in the light of Islamic Jurisprudence to elude all the conflicts and debates. It paves the way for a lay muslims to sail smooothly through the perilous and puzzling waves of modern era. Photos have become a part of life and it is necessary for a Muslim to do whatever he does within the realm of Sharia.